TELAAH HISTORIS PERTUMBUHAN PUSAT PENDIDIKAN ISLAMDI JAWA SAMPAI PERIODE PERANG JAWA - Untung, Moh. Slamet (Forum Tarbiyah, 2010)
This paper tries to study and criticize an interesting topic of Islamic education center in Java in the context of history up to the Java War period. There are two important things that will be studied related to the topic, first, the chronology of growth and development of Islam in Java, and second, a center of Islamic education in sociocultural perspective by placing the Java community institutions such as the center of education activity. The dynamics of growth and development of Islamic educational institutions are influenced by not only internal factors of the founders, but also the external factors that are global. Accumulatively - integratively, both effects fuse and produce a format and style of Islamic educational institutions as will be described through this study.